2017
DOI: 10.1007/s10826-017-0780-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Physical Abuse on Internalizing Behavior Across Generations

Abstract: This study investigated the multigenerational impact of mothers’ own exposure to physical maltreatment on internalizing symptoms in her child after accounting for her parenting practices, depression, and the child’s own exposure to stressful life events. Children (n = 101, ages 5–16), predominantly African American, were recruited into this cross sectional study using ethnographic mapping and targeted sampling for high-risk neighborhoods. Mothers reported retrospectively on their own exposure to physical maltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 47 publications
(57 reference statements)
1
34
0
1
Order By: Relevance
“…The variables used in this study (except age and gender) were self-reported, thus we cannot rule out the possible presence of reporting error (Hepp et al, 2006;Jivraj et al, 2017;Sheikh, 2017a). The test-retest reliability of parental history of psychological problems was not high, which raises the concern that we were not able to fully control for genetic dispositions (Esteves et al, 2017).…”
Section: Discussionmentioning
confidence: 86%
“…The variables used in this study (except age and gender) were self-reported, thus we cannot rule out the possible presence of reporting error (Hepp et al, 2006;Jivraj et al, 2017;Sheikh, 2017a). The test-retest reliability of parental history of psychological problems was not high, which raises the concern that we were not able to fully control for genetic dispositions (Esteves et al, 2017).…”
Section: Discussionmentioning
confidence: 86%
“…The majority of the 9,502 respondents were aged 45 years and above (61.5%), were female (52.8%), and were living with a spouse (83.9%) ( Genetic influences [59,60], ACEs [1, 6-8, 56, 61], environmental exposures, and ongoing stress are factors that combine to determine how an individual responds to stress, as well as their vulnerability to psychopathology in adulthood [11,51,62]. Accordingly, it is important to determine whether the mediated effect (indirect effect) is due to dissatisfaction with friendships or some other unmeasured or unaccounted-for variable [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Meta analisis yang dilakukan Gershoff dan Grogan-Kaylor (2016) memperlihatkan bahwa hukuman fisik yang diberikan oleh orang tua dapat berdampak pada tumbuh kembang anak. Kesehatan mental seperti stres, depresi, menurunnya rasa percaya diri anak, serta meningkatkan perasaan malu, dan ketidakberdayaan merupakan beberapa dampak internalisasi (internalizing) pada anak (Esteves et al, 2018;Gershoff & Grogan-Kaylor, 2016).…”
Section: Penelitianunclassified